Uporabnost umetne inteligence v sodobni fitoterapiji - Injac, Rade (Farmacevtski vestnik, 2025)
The integration of artificial intelligence into modern phytotherapy enhances traditional approaches to the study of medicinal plants and provides advanced tools for their research, development and clinical application. Artificial intelligence facilitates the rapid and reliable identification of plant species, the analysis of bioactive compounds, predicts their therapeutic effects and optimises formulations for targeted treatments. Artificial intelligence also improves personalisation in phytotherapy by tailoring interventions to individual genetic, metabolic and environmental factors. Despite its undisputed benefits, artificial intelligence also faces challenges such as the insufficient quality of input and output data, the need for interdisciplinary collaboration, and ethical and regulatory issues that currently limit its use. In this article, we address the key points of integrating artificial intelligence into modern phytotherapy.
Keywords: artificial intelligence; bioactive compounds; Bioaktivne snovi; bioaktivne spojine; Fitoterapija; medicinal plants; phytotherapy; Umetna inteligenca; Zdravilne rastline